(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
The article deals with the analysis of the spectacle SóFridas by Trip Teatro (Rio do Sul/SC), in the light of gender theories, such as feminisms and loving and maternal devices (Zanello, 2018). It addresses the language of Objects Theater, emphasizing the metaphors and symbologies evoked in the scene. It observes the ways in which dramaturgy finds echoes in the personal stories of several women, understanding the spectacle as an anti-gender technology (Lauretis, 1984), and feminist theater (Miranda, 2019) by questioning standards and conduct related to women.